The purity myth : how America's obsession with virginity is hurting young women - Valenti, Jessica (Seal Press, 2009)
"The United States is obsessed with virginity - from the media to schools to government agencies. The Purity Myth is a critique about why this is so, and why it's problematic for girls and women. Analyzing cultural stereotypes and media messages, Jessica Valenti reveals the overt and hidden ways our society links a young woman's worth to her sexuality rather than to values like honesty, kindness, and altruism"--Jacket